A Feminist-Psychoanalytic Reading of Charlotte Perkins Gilman’s “The Yellow Wallpaper: A Textual Analysis - Addai-Amoah, Anthony Kwarteng; Sebesho, Molebogeng (Journal of Language and Literature Studies, 2026)
This study approaches Charlotte Perkins Gilman’s “The Yellow Wallpaper” from a feminist-psychoanalytic perspective, examining how the act of writing serves as a mode of resistance for a woman silenced by patriarchal and medical authority. Through a close textual analysis informed by Freudian psychoanalytic concepts, the paper examines how Gilman constructs a psychological portrait of female confinement and rebellion. The narrator’s descent into madness is interpreted as both a symptom of the patriarchal suppression of female desire and an unconscious revolt against it. Gilman’s use of symbolism—the yellow wallpaper, the barred windows, and the creeping woman- encodes the internalisation of patriarchal control and the protagonist’s struggle to reclaim her identity. The study also examines the gendered power dynamics between the female protagonist and her husband, a physician, situating the story within the broader social and cultural context of nineteenth-century America. In effect, this paper argues that Gilman transforms “The Yellow Wallpaper” [3] into a timeless work of psychological and feminist insight, showing how literature can illuminate the human mind and the structures that shape it.